Being proven wrong elicits learning in children – but only in those with higher executive function skills. Issue 3 (30th October 2019) - Brod, Garvin; Breitwieser, Jasmin; Hasselhorn, Marcus; Bunge, Silvia A.
Abstract: This study investigated whether prompting children to generate predictions about an outcome facilitates activation of prior knowledge and improves belief revision. 51 children aged 9–12 were tested on two experimental tasks in which generating a prediction was compared to closely matched control conditions, as well as on a test of executive functions (EF). In Experiment 1, we showed that children exhibited a pupillary surprise response to events that they had predicted incorrectly, hypothesized to reflect the transient release of noradrenaline in response to cognitive conflict. However, children's surprise response was not associated with better belief revision, in contrast to a previous study involving adults. Experiment 2 revealed that, while generating predictions helped children activate their prior knowledge, only those with better inhibitory control skills learned from incorrectly predicted outcomes. Together, these results suggest that good inhibitory control skills are needed for learning through cognitive conflict. Thus, generating predictions benefits learning – but only among children with sufficient EF capacities to harness surprise for revising their beliefs. Abstract : Violated predictions are considered key drivers for learning, but it is unclear whether children can harness the resulting surprise signal for revising incorrect beliefs. The current study tested this assumption in children aged 9–11 using a prediction–feedback learning task along with recordings of pupillary responses. We found that children's ability to harness surprise for belief revision was strongly and specifically related to their inhibitory control capacity.